Endometriosis of the sciatic nerve with cyclic sciatica - Baskan, Ozdil; Ozdemir, Ferda (Acta medica Lituanica, 2014)
Endometriosis is an important gynecological disorder which is characterized by proliferation of the functional endometrial tissue outside the uterine cavity, affects most commonly the ovaries and less frequently the gastrointestinal tract, chest, urinary tract, and soft tissues. Endometriosis invading the sciatic nerve is a rare manifestation of a common disease. The cyclic rhythm of pain, associated with the magnetic resonance imaging (MRI) signal of the lesion should suggest a diagnosis of endometriosis. Early diagnosis and treatment are important to prevent irreversible damage to the sciatic nerve.